Micro-X-ray-CT for analysis of particle size segregation during powder spreading in Binder Jet Printing - Julia G. Behnsen; Joseph W. Roberts; Oliver J. Rogan; James M. McArdle; Kate Black (Additive Manufacturing Letters)
The uniformity of the powder bed in Binder Jet Printing can impact the final properties of additively manufactured components. Granular flow phenomena, such as particle size segregation can influence the uniformity of the powder bed. Due to the 3D nature of the powder bed and the standard requirement for sintering parts following printing, direct experimental observation of the particle distribution and packing density can be difficult. The use of Micro-X-ray-CT however, enables the high-resolution imaging of components manufactured by binder jetting and allows quantification of particle size distribution and packing density throughout the powder bed. This study analyses the periodicity of effects such as in-layer particles size segregation and packing density. The results presented here show that particles segregate by size within each layer of the binder jet printed sample, which resulted in a periodic density change within each layer. The particle size distribution changes over the length of the power-bed, with the volume fraction of smaller particles increased near the front of the powder bed, and the volume fraction of larger particles increased near the back. The insights gained from the Micro-X-ray-CT characterisation approach allow for an enhanced understanding of the powder spreading process in additive manufacturing, paving the way forward for possible part optimisation.